2020
DOI: 10.1136/bmjsem-2019-000662
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia is not the primary mechanism contributing to exercise-induced proteinuria

Abstract: IntroductionProteinuria increases at altitude and with exercise, potentially as a result of hypoxia. Using urinary alpha-1 acid glycoprotein (α1-AGP) levels as a sensitive marker of proteinuria, we examined the impact of relative hypoxia due to high altitude and blood pressure-lowering medication on post-exercise proteinuria.MethodsTwenty individuals were pair-matched for sex, age and ACE genotype. They completed maximal exercise tests once at sea level and twice at altitude (5035 m). Losartan (100 mg/day; ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…The coupling between desaturation and attenuated postexercise α1-AGP excretion in HYP observed in this study supports earlier cycling-based studies that have demonstrated similar reductions ( 7 ) or unchanged postexercise excretion in hypoxia ( 28 ). The present observations were attributed to concomitant reductions in exercise performance known to accompany hypoxic exercise ( 29 ), which have, in part, been attributed to reductions in blood flow to the working limbs ( 30 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The coupling between desaturation and attenuated postexercise α1-AGP excretion in HYP observed in this study supports earlier cycling-based studies that have demonstrated similar reductions ( 7 ) or unchanged postexercise excretion in hypoxia ( 28 ). The present observations were attributed to concomitant reductions in exercise performance known to accompany hypoxic exercise ( 29 ), which have, in part, been attributed to reductions in blood flow to the working limbs ( 30 ).…”
Section: Discussionsupporting
confidence: 91%
“…Normality of distribution was assessed using Shapiro–Wilk test for each outcome measure with data log-transformed where possible and outliers removed (using ROUT method) where appropriate (for normally distributed data) before analysis. For reference, raw α1-AGP excretion data were reported, however, analyses for urinary α1-AGP were conducted using log-transformed values as previously described ( 7 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further details of participant genotype pairing, losartan administration and ascent profile have been previously published as part of another study conducted on this expedition. 15 …”
Section: Methodsmentioning
confidence: 99%
“…Further details of participant genotype pairing, losartan administration and ascent profile have been previously published as part of another study conducted on this expedition. 15 Baseline and daily measures Baseline measures of BP and exercise performance were recorded at sea-level and before losartan/placebo administration (~4 weeks prior to ascent). During ascent, measures of resting systolic and diastolic BPs (SBP and DBP) were collected each morning using a manual sphygmomanometer as part of the routine medical examination.…”
Section: Materials and Methods Design And Participantsmentioning
confidence: 99%